2018
DOI: 10.1038/s41598-018-24644-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic (idiopathic) epilepsy with photosensitive seizures includes features of both focal and generalized seizures

Abstract: Clinically, some patients having genetic (idiopathic) epilepsy with photosensitive seizures were difficult to be diagnosed. We aimed to discuss whether the genetic (idiopathic) epilepsy with photosensitive seizures is a focal entity, a generalized entity or a continuum. Twenty-two patients with idiopathic epilepsies and photoconvulsive response (PCR) were retrospectively recruited. In the medical records, the seizure types included “generalized tonic-clonic seizures (GTCS)” in 15, “partial secondarily GTCS (PG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 31 publications
2
16
0
Order By: Relevance
“…We add to the literature an "electronegative'' response to photic stimulation that may serve as a pitfall for an accurate interpretation of epilepsy. While the mechanisms involved in generation of a PPR are poorly understood, genetic influences are felt to play an important role [4]. However, this was absent in our patient with extratemporal focal epilepsy.…”
Section: Non-physiologicmentioning
confidence: 64%
“…We add to the literature an "electronegative'' response to photic stimulation that may serve as a pitfall for an accurate interpretation of epilepsy. While the mechanisms involved in generation of a PPR are poorly understood, genetic influences are felt to play an important role [4]. However, this was absent in our patient with extratemporal focal epilepsy.…”
Section: Non-physiologicmentioning
confidence: 64%
“…Typically seizures are not suppressible, and following commands is not possible during generalized events. However, photosensitive seizures may have atypical features, 9 including possible volitional induction, or as demonstrated in case 2, preserved awareness. These unusual aspects that are more typical of tics and stereotypies may lead to misdiagnosis.…”
Section: Discussionmentioning
confidence: 96%
“…Photosensitivity is usually observed in genetic (idiopathic) generalized epilepsy, with PPR characterized by generalized epileptiform discharges ( 8 ). However, a growing number cases of focal seizures induced by IPS have been reported, almost originating from the occipital lobe ( 9 , 10 ). Furthermore, cases of photosensitive focal seizures starting at the temporal lobe have also been reported ( 4 , 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a series of patients with genetic (idiopathic) generalized epilepsy, focal interictal discharges and focal seizures had been observed in 35% of patient population ( 20 ). In our previous studies of idiopathic epilepsy with photosensitive seizures, more than 70% of patients' PCR had FBTCS derived from the occipital lobe, and 50% of patients' PCR had myoclonic seizures with comprehensive network activation ( 9 ). In our study, PPR of all patients mainly showed generalized discharges.…”
Section: Discussionmentioning
confidence: 99%